The Mesoproterozoic Hallandian event - a region-scale orogenic event in the Fennoscandian Shield - Brander, Linus (2011)
The Sveconorwegian Province occupies the southwestern part of the Fennoscandian Shield. The easternmost tectonic unit of the Province is the 1710-1660 Ma parautochthonous Eastern Segment, which bears the imprint of at least two metamorphic events; the 1460-1380 Ma Hallandian and the 1150-970 Ma Sveconorwegian. However, the nature and extent of the Hallandian event have been difficult to access due to the Sveconorwegian, effectively masking earlier metamorphic assemblages, structures and relations between rock units. This thesis aims to characterize the Hallandian event by investigating pre-Sveconorwegian deformation and metamorphism in an area of the Eastern Segment that largely escaped later Sveconorwegian reworking. These results are then considered in a regional perspective and related to ~1.45 Ga magmatism and metamorphism observed elsewhere in Fennoscandia. Considering the compiled data from this time period, it now appears that the Hallandian event indeed was a true orogenic event that affected a large portion of the Fennoscandian Shield. In the study area, located within the Protogine Zone in the eastern part of the Eastern Segment near Jönköping, Sveconorwegian reworking is restricted to discrete, N-S trending shear-zones. Between these shear-zones, structures, mineral assemblages and geochronological information from pre-Sveconorwegian events are preserved. The first paper provides field, mineral and chemical characteristics, as well as a baddeleyite U-Pb crystallization age of 1455±6 Ma for the Jönköping Anorthositic Suite which is abundant across the study area as small intrusive bodies. In these plagioclase-porphyritic and equigranular anorthositic rocks, deformation is restricted to thin, E-W-trending shear-zones. In the second paper we investigate the deformed country-rocks and date metamorphism and the development of the E-W to SE-NW trending gneissic fabric at 1450-1400 Ma, using U-Pb secondary ion mass spectrometric (ion probe) analysis of complex zircons. The folding event is bracketed between ...